Indigenous Global Art Project
Children's artwork, various nationalities, painting, singing, participants: Ghandi School Hungary, Bairnsdale Primary School Australia, Baan Nu-Se-Plo School Thailand, pearl River Elementary School U.S.A., Sunny Side Elementary School U.S.A., Woolum Bellum Koorie Open Door Education Australia, Taos Peublo Day School U.S.A., Gypsy College Hungary, A:Schiwi Elementary School U.S.A., Bairnsdale Secondary College Australia